2015
DOI: 10.1038/ncomms7675
|View full text |Cite
|
Sign up to set email alerts
|

A megacomplex composed of both photosystem reaction centres in higher plants

Abstract: Throughout the history of oxygen evolution, two types of photosystem reaction centres (PSI and PSII) have worked in a coordinated manner. The oxygen evolving centre is an integral part of PSII, and extracts an electron from water. PSI accepts the electron, and accumulates reducing power. Traditionally, PSI and PSII are thought to be spatially dispersed. Here, we show that about half of PSIIs are physically connected to PSIs in Arabidopsis thaliana. In the PSI-PSII complex, excitation energy is transferred effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
111
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(121 citation statements)
references
References 30 publications
9
111
1
Order By: Relevance
“…It has been proposed that, in the grana margin regions, which harbor LHCII and both photosystems, LHCII can migrate rapidly between them (Albertsson et al, 1990;Albertsson, 2001). This idea is supported by the recent discovery of mega complexes containing both photosystems in the grana margin regions (Yokono et al, 2015). Furthermore, phosphorylation of LHCII was found to increase not only the amount of PSI found in the grana margin region of thylakoid membranes (Tikkanen et al, 2008a), but also to modulate the pattern of PSI-PSII megacomplexes under changing light conditions .…”
supporting
confidence: 54%
“…It has been proposed that, in the grana margin regions, which harbor LHCII and both photosystems, LHCII can migrate rapidly between them (Albertsson et al, 1990;Albertsson, 2001). This idea is supported by the recent discovery of mega complexes containing both photosystems in the grana margin regions (Yokono et al, 2015). Furthermore, phosphorylation of LHCII was found to increase not only the amount of PSI found in the grana margin region of thylakoid membranes (Tikkanen et al, 2008a), but also to modulate the pattern of PSI-PSII megacomplexes under changing light conditions .…”
supporting
confidence: 54%
“…However, Lhcb1 is more phosphorylated in large PSII-rich supercomplexes solubilized with digitonin from stromal lamellae and grana margins, whereas its level of phosphorylation in PSII-LHCII supercomplexes extracted with b-DM from grana cores is comparatively low (Fig. 6; Yokono et al, 2015). These observations suggest that Lhcb phosphorylation may contribute to the movement of the PSII-LHCII supercomplexes from grana cores toward lessstacked domains of the thylakoid membrane, grana margins, and stromal lamellae.…”
Section: Antenna Phosphorylation In the Psii-lhcii Supercomplexesmentioning
confidence: 60%
“…A relatively high level of Lhcb1 and Lhcb2 phosphorylation was observed in the Sc4b band and in the Mc5b band. Both were described to contain PSI, PSII, and LHCII, but fluorescence lifetime analysis indicated that PSII may not be functionally connected to PSI in these bands (Järvi et al, 2011;Yokono et al, 2015).…”
Section: Phosphorylation Of Antenna Isoforms In Different Supercomplexesmentioning
confidence: 99%
“…Moreover, the traditionalstate transition model is based on lateral segregation of PSII-LHCII and PSI-LHCI to different thylakoid domains. It, however, seems likely that PSII and PSI are energetically connected through a shared light-harvesting system composed of LHCII trimers (Grieco et al, 2015), and there is efficient excitation energy transfer between the two photosystems (Yokono et al, 2015). Nevertheless, it is clear that LHCII phosphorylation is a prerequisite to form an isolatable PSI-LHCII complex called the state transition complex (Pesaresi et al, 2009;Järvi et al, 2011).…”
mentioning
confidence: 98%